Percutaneous endoscopy-guided gallbladder lumen-apposing metal stent retrieval, lithotripsy, and cholecystoduodenal stenting in a patient with acute cholecystitis - Shahaan Shafi, BS; Ali Husnain, MD; Ahsun Riaz, MD (Radiology Case Reports)
Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) with lumen apposing metal stent (LAMS) has emerged as an effective alternative to percutaneous cholecystostomy in managing acute cholecystitis patients with contraindications to open or laparoscopic cholecystectomy. Herein, the authors describe a case of a 69-year-old male who presented to interventional radiology with sepsis due to acute calculous cholecystitis and LAMS migration into the gallbladder. After stabilizing the patient with percutaneous cholecystostomy, percutaneous cholecysto-lithotripsy/lithectomy, cholecystoduodenal stenting, and LAMS retrieval were performed. This report highlights the potential complications associated with EUS-GBD with LAMS insertion and contributes to the limited literature on percutaneous management of migrated LAMS.